A friction study on automotive connecting-rod big end journal bearing lubrication system - Chu, Jun Hao, 1994-, author; Chong, William Woei Fong, supervisor; Fakulti Kejuruteraan Mekanikal (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Sains (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2018